2014 ESC/ESA GUIDELINES ON NON-CARDIAC SURGERY: CARDIOVASCULAR ASSESSMENT AND MANAGEMENT - (ESC) European Society of Cardiology; (ESA) European Society of Anaesthesilogy (Российский кардиологический журнал, 2015)
The  Joint  Task  Force  on  non-cardiac surgery:  cardiovascular assessment  and  management of the  European  Society of Cardiology (ESC) and the European Society of Anaesthesiology  (ESA)